Análise dos efeitos de crises em ações de valor e ações de crescimento no mercado brasileiro - Paiva, Antonio Claudio Noberto (Universidade do Vale do Rio dos Sinos, 2023)
This study aimed to analyze the influence of crises on value stocks and growth stocks of B3 and IBOVESPA, using the three-factor model according to Fama and French (1992). In order to respond to the objective of this study, data were collected on the economática® platform of B3 and IBOVESPA companies in the period from 2005 to 2021. The research hypotheses were tested using the multiple regression model in a similar way to that used by Fama and French (1992), adding crisis dummy variables. The result obtained confirms the hypothesis that the price of IBOVESPA growth shares had a higher return than value shares during the COVID19 crisis period. Therefore, the results of this thesis indicate that the COVID crisis had a greater positive impact on the price of growth stocks.
Keywords: Crises; Ações de valor; Ações de crescimento; B3; Value stocks; Growth stocks; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis